Functional results of surgical treatment of macular holes fully preserving the internal limiting membrane as compared with the traditional method - P. V. Lyskin; P. L. Volodin; I. R. Makarenko (Российский офтальмологический журнал, 2023)
Purpose: to assess the functional results of surgical treatment of macular holes (MH) using the authors’ developed technology preserving the internal limiting membrane (ILM) and compare them with the results of traditional surgery technology involving ILM peeling.Material and methods: 150 MH patients aged 50 to 82 were divided into 2 groups: the main group who underwent surgical MH treatment with ILM preservation and the control group, whose traditional surgical treatment involved ILM peeling. After vitrectomy, the main group patients’ macular areas were treated with a bacterial collagenase solution (1 kU) for three minutes, whereupon it was washed out, the vitreal cavity was dried and treated with platelet-rich plasma. In the control group, ILM was stained and removed, whereupon platelet-rich plasma was applied in the air medium. The anatomical result was assessed by optical coherence tomography data. To assess the functional results, the patients were tested for the best corrected visual acuity (BCVA) and subjected to microperimetry. The observation period was 24 months.Results: in all cases, a significant increase in BCVA was achieved after surgical treatment. After 6 months, the control group showed a tendency to a BCVA decrease, while in the main group BCVA remained stable. In the main group, not a single case showed a decrease in the total retinal photosensitivity below the threshold level of the norm of 24 dB, whilst in the control group, 35 cases (47 %) revealed a retinal sensitivity decrease below 24 dB. The total retinal sensitivity turned out to be significantly lower in the control group as compared to the main group over the entire observation period (p < 0.05). Postoperative scotomas were significantly more frequent after ILM peeling. Absolute scotomas were detected in 7 control group cases, whilst in the main group they were not noted in any case.Conclusion. The developed technology makes it possible to practically eliminate the formation of absolute scotomas and to significantly reduce the formation of relative scotomas in the postoperative period, as well as improve functional results against the traditional method of surgical treatment of MH with ILM peeling.